Assessing The Role of the Endocaanbinoid System in Arsenic-Induced Neurotoxicity - Cross, Monica Nicole (My University, 2024)
The endocannabinoid system (ECS) is an important brain pathway that plays a major role in early brain development and neural circuitry. The ECS has been found to regulate stress and emotional behavior during development. It modulates neural and behavioral stress and has also been found to be affected by stress exposure. The endocannabinoid system is a biological system that includes endocannabinoids and cannabinoid receptor proteins. Cannabinoid receptor 1 (CB1) has been found to control excitatory and inhibitory synaptic strength. The balance of these strengths is important and an imbalance in the strengths can contribute to autism spectrum disorder, epilepsy, and schizophrenia. Arsenic is a natural found heavy metal in air, water, and soil. It can disrupt the ECS by second- hand smoke, water contaminations, and industrial processes. Studies on arsenic's effects on the ECS are limited, but it is important to know the correlation between developmental defects and arsenic toxicities. iPSC in vitro 40 days neural organoid differentiation model mimics early brain development especially the 1st trimester during pregnancy.
Keywords: Neurology; Endocannabinoid system; Neural Organoids